MEASUREMENTS OF CYCLOTRON FEATURES AND PULSE PERIODS IN THE HIGH-MASS X-RAY BINARIES 4U 1538-522 AND 4U 1907+09 WITH THE INTERNATIONAL GAMMA-RAY ASTROPHYSICS LABORATORY - Hemphill, Paul B.; Rothschild, Richard E.; Caballero, Isabel; Pottschmidt, Katja; Kühnel, Matthias; Fuerst, Felix; Wilms, Jörn (Astrophysical Journal, 2013)
We present a spectral and timing analysis of International Gamma-Ray Astrophysics Laboratory (INTEGRAL) observations of two high-mass X-ray binaries, 4U 1538-522 and 4U 1907+09. Our timing measurements for 4U 1538-522 find the pulse period to have exhibited a spin-up trend until approximately 2009, after which there is evidence for a torque reversal, with the source beginning to spin down to the most recently measured period of 525.407 +/- 0.001 s. The most recent INTEGRAL observations of 4U 1907+09 are not found to yield statistically significant pulse periods due to the significantly lower flux from the source compared with 4U 1538-522. A spectral model consisting of a power-law continuum with an exponential cutoff and modified by two cyclotron resonance scattering features is found to fit both sources well, with the cyclotron scattering features detected at similar to 22 and similar to 49 keV for 4U 1538-522 and at similar to 18 and similar to 36 keV for 4U 1907+09. The spectral parameters of 4U 1538-522 are generally not found to vary significantly with flux and there is little to no variation across the torque reversal. Examining our results in conjunction with previous work, we find no evidence for a correlation between cyclotron line energy and luminosity for 4U 1538-522. 4U 1907+09 shows evidence for a positive correlation between cyclotron line energy and luminosity, which would make it the fourth, and lowest luminosity, cyclotron line source to exhibit this relationship.
Keywords: pulsars: individual (4U 1538-522; 4U 1907+09); stars: magnetic field; stars: oscillations; X-rays: binaries; X-rays: stars